HPLC Chromatographic Analysis Antioxidant activity of seeds some varieties of prickly pear (Opuntia ficus-indica L.) from the Sidi-Fredj souk Ahras Algeria - BOUAOUICH , Abderrahmane; Bouguerche, Faiza (Algerian Journal of Biosciences, 2022)
The study was conducted on seeds of three varieties of Opuntia ficus-indica (O. ficus-indica), harvested from different regions of Souk Ahras North-East (Sidi-Fredj, Taoura and Drea) of Algeria). The analysis consisted of antioxidants extraction, following the solid-liquid extraction with ethanol 40% (v/v), their quantification and determination of their antioxidant activity by two methods (reducing power and DPPH• Test). Results show that total phenolic content (TPC) ranged from 74.04 to 92.83 mg GAE /100g Extract. The Sidi-Fredj variety has the best rate followed, by the Taoura and Drea ones. Concerning, flavonoids and tannins, the Taoura variety contains higher concentrations corresponding to 2.67 mg QE/100g and 6.60mg CE/100g. activities of extracts of three varieties show similar performance; the EC50 for the reduction of ferric iron 0.05g/mL for all extracts, whereas the EA is more important in Sidi-Fredj and Drea seeds extracts. Regarding the scavenging of DPPH •, Drea and Sidi-Fredj varieties show the highest capacity equals to 0.20g/mL. Linear correlations between the different studied activities and some antioxidants (flavonoids, tannins) rates were noticed; indicating their participation in the obtained effect. Analysis of the oil by HPLC revealed the presence of phenolic compounds including gallic acid and a form of vitamin E (α-tocophérol), capable of expressing biological activities; Anti-oxidants and vitamins. CPG analysis showed that prickly pear oil was a major source of essential fatty acids (C18 :2 and C18 :3).The seeds extract present therefore a variety effect with properties that should be taken intconsideration for possible other exploitation in addition to the oil one.